Gender Differences in Patterns and Correlates of Concurrent Substance Use Among Patients in Methadone Maintenance Treatment - Arnold, Tomorrow D. (Subst Use Misuse, 2021)
BACKGROUND: Continued substance use is common during opioid use disorder (OUD) treatment. There are still inconsistencies in how continued substance use and concurrent patterns of substance use among patients with OUD varies by gender. There is still more to learn regarding how factors associated with continued and concurrent use might differ for men and women in methadone maintenance treatment (MMT). METHODS: This cross-sectional study examined predictors of concurrent substance use subgroups among patients receiving MMT. The sample included 341 (n = 161 women) MMT patients aged 18 and older from opioid treatment programs in Southern New England and the Pacific Northwest. Patients completed a survey assessing sociodemographic and clinical characteristics including past-month substance use. Latent class analyses were conducted by gender to identify groups based on substance use and determine predictors of those classes. RESULTS: Three-class solutions were the optimal fit for both men and women. For both genders, the first subgroup was characterized as Unlikely Users (59.8% women, 52.8% men). Classes 2 and 3 among women were Cannabis/Opioid Users (23.7%) and Stimulant/Opioid Users (13.0%). Among men, Classes 2 and 3 consisted of Alcohol/Cannabis Users (21.9%) and Cannabis/Stimulant/Opioid Users (25.3%). Ever using Suboxone (buprenorphine/naloxone) and depression/anxiety symptoms were significantly linked to substance use group among women, whereas homelessness and employment status were significantly associated with substance use group among men. CONCLUSIONS: This study furthers understanding of gender differences in factors associated with continued substance use and distinctive patterns of concurrent substance use that may guide tailored treatments among patients MMT.